من لسانيات الجملة إلى لسانيات النص - سهل, ليلى (University of El-oued, 2018)
جاءت هذه الدراسة لتوضّح أكبر نقلة في اللسانيات، أبسط ما يقال عنها أنّها كشفت عن ضيق شديد في الدراسات التي اعتمدت على الجملة. واعتبرتها الوحدة اللغوية الكبرى خاصة في الدراسات الأدبية، فيعتبر هذا نبذا للنموذج القديم وإحلال جديد محلّه، أو تطور جدلي مستمر متصاعد. This study came to illustrate the greatest move in the linguistics, the simplest thing that we can say about it is that it has revealed a great narrowness in the studies that relied on the sentence. And considered it the biggest linguistic unit, especially in the literary studies, and this is a renounce of the old model and replaced it with a new one, or a continuous dialectical development
مقال. Ex Professo. مج3. ع.1. جامعة الوادي
Keywords: اللسانيات; الدراسات الأدبية; دراسات الجملة